Complementary pharmacological and toxicological characterization data on the pharmacological profile of N-(2,6-dichlorophenyl)-2-(4-methyl-1-piperidinyl) acetamide - Myrna Déciga-Campos; Gabriel Navarrete-Vázquez; Francisco Javier López-Muñoz; Tadeusz Librowski; Amanda Sánchez-Recillas; Victor Yañez-Pérez; Rolffy Ortiz-Andrade (Data in Brief, 2016)
This text presents complementary data corresponding to pharmacological and toxicological characterization of N-(2,6-dichlorophenyl)-2-(4-methyl-1-piperidinyl)acetamide (LIA) compound. These data support our research article entitled “Pharmacological profile of N-(2,6-dichlorophenyl)-2-(4-methyl-1-piperidinyl)acetamide, a novel analog of lidocaine” Déciga-Campos M., Navarrete-Vázquez G., López-Muñoz F.J., Librowski T., Sánchez-Recillas A., Yañez-Pérez V., Ortiz-Andrade R. (2016) [1]. Toxicity was predicted through the ACD/ToxSuite software and evaluated in vivo using brine shrimp larvae (Artemia salina L.) and mice. Also, we used the micronucleus assay to determine genotoxicity. We used the platform admetSAR to predict absorption properties of LIA and lidocaine. Keywords: N-(2,6-dichlorophenyl)-2-(4-methyl-1-piperidinyl)acetamide, Toxicity, Lidocaine